2017
DOI: 10.1039/c7ra05444k
|View full text |Cite|
|
Sign up to set email alerts
|

Eosin Y catalysed photoredox synthesis: a review

Abstract: In recent years, photoredox catalysis using eosin Y has come to the fore front in organic chemistry as a powerful strategy for the activation of small molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
179
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(182 citation statements)
references
References 68 publications
1
179
0
2
Order By: Relevance
“…[12] From ac onceptual standpoint, we wondered whether organic photoredox catalysis [13] might be used to leverage the orthogonality of transition-metal-catalyzed C(sp 2 ) À SeCF 3 bond formation under mild reaction conditions. [14] We envisioned the use of arene diazonium salts that exhibit mild reduction potentials.T his class of substrates can easily be prepared from readily available anilines.N ext, we selected eosin Y [15] as an organic photocatalyst, which is known as ap otential reducer for arene diazonium salts.T he first test was performed by mixing the diazonium salt 1a with our shelf-stable reagent I in the presence of 5mol %ofeosin Yin DMSO at room temperature under irradiation of aw hite LED lamp.T his initial attempt led to the formation of the desired product in 77 %yield (Table 1, Entry 1). Theproduct was also formed in DMF as solvent although with as ignificantly lowered yield of 42 %(Table 1, Entry 2).…”
mentioning
confidence: 99%
“…[12] From ac onceptual standpoint, we wondered whether organic photoredox catalysis [13] might be used to leverage the orthogonality of transition-metal-catalyzed C(sp 2 ) À SeCF 3 bond formation under mild reaction conditions. [14] We envisioned the use of arene diazonium salts that exhibit mild reduction potentials.T his class of substrates can easily be prepared from readily available anilines.N ext, we selected eosin Y [15] as an organic photocatalyst, which is known as ap otential reducer for arene diazonium salts.T he first test was performed by mixing the diazonium salt 1a with our shelf-stable reagent I in the presence of 5mol %ofeosin Yin DMSO at room temperature under irradiation of aw hite LED lamp.T his initial attempt led to the formation of the desired product in 77 %yield (Table 1, Entry 1). Theproduct was also formed in DMF as solvent although with as ignificantly lowered yield of 42 %(Table 1, Entry 2).…”
mentioning
confidence: 99%
“…The oxidation and reduction potentials of the thiophenol were observed at −0.37 V and −1.3 V respectively. The redox potential of Eosin Y indicates that it could allow a single electron oxidation of the thiophenol but not the reduction . Also, thermodynamically a single electron oxidation of the thiophenol ( E PhSH/PhSH +≈0.95 V vs. SCE) by the excited state of Eosin Y ( E E*/E− =1.18 V vs. SCE) is quite feasible …”
Section: Resultsmentioning
confidence: 99%
“…Such reactions operating at room temperature have allowed various otherwise tediousr eactions.O rganicd yes present ar ational and rather economic preference over the metal-based photocatalysts for thiolation process, considering the fact that coordinationo ft hiols could poison the metal catalysis. [16] Eosin Yi sa mongst the well explored organic dyes for photo-redox organic transformations as the redoxp otentialo fE osin Ys uits well for both the oxidation as well as reduction of organic substrates, [17] thereby rendering av ast range of substrate scopef or the desired transformations. In this perspective, it is envisioned that aS ET strategy could be effective by activated Eosin Yu nder visible light for the CÀSb ond formation employing hydrazones and thiophenols.…”
Section: Introductionmentioning
confidence: 99%
“…Literature surveys reported that the mono or di anionic forms of eosin Y are capable of interacting with a cationic form of the drug molecules by the electrostatic interaction and hydrophobic forces and forms either binary complex with drug molecule or a ternary complex with drug molecule and a metal [8]. In recent years, eosin was used as photoredox catalyst in organic synthesis [9], Carbon-Carbon and Carbon-Phosphorous bond formation [10].…”
Section: Fig 1: Structure Of Eosinsmentioning
confidence: 99%